Influence of Proton Conducting Cations on the Structure and Properties of 2D Anilate-Based Magnets - Palacios Corella, Mario; Fernández Espejo, Alejandro; Bazaga-García, Montse; Ramírez-Losilla, Enrique; Cabeza-Díaz, Aurelio; Clemente-León, Miguel; Coronado, Eugenio (ACS publications, 2017)
The syntheses, structures, magnetic, and proton conductivity properties of a family of bimetallic anilate-based compounds with inserted alkylammonium cations are presented. The structures of (Me2NH2)[MnIICrIII(Br2An)3]·2H2O (1), (Et2NH2)[MnIICrIII(Br2An)3] (2), (Et3NH)[MnIICrIII(Cl2An)3] (3), and [(Et)(i-Pr)2NH]-[MnIICrIII(Br2An)3]·(CHCl3)0.5·(H2O) (4) contain a 2D anionic network formed by Mn(II) and Cr(III) ions linked through anilate ligands. In 1, 2, and 3, the hexagonal holes of this network are occupied by Me2NH2+, Et2NH2+, or Et3NH+ cations. Interestingly, the small increase of size of the templating cation in 4 ([(Et)(i-Pr)2NH]+ in the place of Me2NH2+, Et2NH2+ or Et3NH+), gives rise to a different structure with half of the cations placed within the layers and the other one in the space between the layers. This leads to bilayers with an interlayer separation similar to those of 1, 2, and 3 separated by larger interbilayer distances. Compounds 1, 2, and 3 show a ferrimagnetic ordering with a Tc of 8.0 K (1), 8.9 K (2), and 8.0 K (3). In 4, the presence of different interlayer distances leads to a metamagnetic behavior when the sample is measured in contact with the mother liquor. The behavior changes in the dry sample, which shows a ferrimagnetic ordering as that of 1, 2, and 3 due to collapse of the structure as confirmed by powder X-ray diffraction. Interestingly, the metamagnetic behavior is recovered after reimmersing the crystals in the mother liquor proving the reversibility of the process. All solids are Grotthuss-type proton conductors with conductivity values ranging between 2.3 × 10−6 S·cm−1 for 3 and 2.4 × 10−5 S·cm−1 for 1 measured at 70 °C and 95% relative humidity and activation energies of ∼0.2 eV.
Keywords: Imanes superconductores; Espectroscopía; Aniones; Anilate-Based Magnets; 2,5-Dihydroxy-1,4-benzoquinone Dianion Derivatives; Proton-conductivity